Analisis Faktor-Faktor yang Mempengaruhi Manajemen Laba pada Perusahaan Manufaktur Sektor Tekstil dan Garment yang terdaftar di BEI Tahun 2011-2015 - Mohammad Nur Azis; Rizqo Suci Saputri (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2016)
The purpose of this study is to analyze the effect of leverage, company size and profitability together on earnings management in the textile and garment sector manufacturing companies listed on the Stock Exchange in 2011-2015. The data collection method used in this study is documentation. While the data analysis method used is the Classical Assumption Test, Simple Linear Regression Analysis, Partial Testing (t-Test), Multiple Linear Regression Analysis, Simultaneous Testing (F Test), Determination Coefficient Analysis (R Square). Some conclusions taken in this study are from the results of the calculation of simple leverage regression testing on earnings management using SPSS obtained sig = 0.847> 0.05 so it can be concluded that leverage does not affect earnings management. From the results of simple regression testing company size measurement of earnings management using SPSS obtained sig =0.016 <0.05 so that it can be concluded that the size of the company influences earnings management. = 0,000 <0,05 so that it can be concluded that profitability has a significant effect on earnings management. From the results of the calculation of multiple regression testing leverage, company size and profitability together on earnings management using SPSS obtained a sig value = 0,000 <0,05 so that it can be concluded that leverage, company size and profitability jointly influence earnings management.